Worker Protection Standard: Records of Employee Safety Training - Frederick M. Fishel (EDIS)
The EPA’s Worker Protection Standard for Agricultural Pesticides (WPS) covers pesticides used in the outdoor and enclosed-space production of plants on farms, forests, and nurseries, as well as greenhouses. The WPS requires agricultural employers to take steps to reduce pesticide-related risks when agricultural workers and pesticide handlers are exposed to these pesticides. The EPA has made several changes to the WPS since it was fully implemented in 1995, and this new 3-page document addresses maintaining records of worker and handler training under the revised WPS, including a sample employee-training verification. Written by Frederick M. Fishel and published by the UF/IFAS Pesticide Information Office. https://edis.ifas.ufl.edu/pi283